Effects of different levels of dried onion powder on nutrient digestibility, biochemical parameters, and nitrogen balance in Wistar albino rats with induced hyperuricemia - Umer, Muhammad; Nisa, Mahr Un; Ahmad, Nazir; Rahim, Muhammad Abdul; Al-Asmari, Fahad (Frontiers in Physiology, 2023)
Introduction: Onion (Allium cepa L.) are excellent sources of bioactive compounds and phytochemicals such as allicin, quercetin, fisetin and other sulphurous compounds. However, our study aimed to investigate the effect of dried onion powder on the hyperuricemia as well as their effects on growth performance, nitrogen balance and biochemical analysis.Methods: 24 rats, six in each group were divided randomly. The group named HU as positive control, HOT1, HOT2 and HOT3 contained onion powder 11.13, 14.84 and 18.61 g/100 g. For the induction of hyperuricemia, a new formulation was developed and administered intraperitoneal (250mg/kg Potassium oxonate) and oral (40mg/kg Potassium bromate) daily for 14 days. After the confirmation of the induction, onion treated diets have various levels of quercetin were offered for 21 days.Results: Significant decreases (P≤0.05) were observed in serum uric acid, alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, total bilirubin, total cholesterol and low-density lipoprotein. Increasing trend (P≤0.05) was shown in hemoglobin, white blood cell, red blood cell and platelet count. Improvement was observed in serum high-density lipoprotein, triglycerides, blood urea This is a provisional file, not the final typeset article nitrogen, serum creatinine, serum total protein and neutrophils, lymphocytes, and monocyte percentages. Positive progress (P≤0.05) was seen in growth performance and nutrient digestibility.In this study, a significantly lower uric acid level was observed in rats fed HOT2 diet and based on the ratio of surface area (Human/Rat), the best recommended dose of onion for the incidence and prevention of hyperuricemia would be 189.95g, accordingly to the dose of quercetin in humans 204 mg/day.